Three New Species of Serjania (Sapindaceae) from South America - Ferrucci, María Silvia (2005)
The new species Serjania chacoensis from Bolivia and Brazil, Serjania souzana from Bolivia, Brazil, and Peru, and Serjania paranensis from the state of Paraná, Brazil, all belonging to Serjania sect. Serjania, are described, illustrated and contrasted to their putatively closest relatives.